Water quality in Istanbul, Marmara Sea - (:unkn) unknown (SCIENTIFIC PUBL-INDIA, 2019)
The Marmara coast in Istanbul, an intensely industrialized and overpopulated city, is a popular center for recreational activities, such as swimming, and fishing. The Kucuksu, Fenerbahce and Suadiye beaches on the Anatolian side of the Marmara coast are highly preferred for swimming and the Sea of Marmara is very important for the diversity of coast organisms. Therefore, this study was conducted to determine whether the seawater quality at the coast is suitable for marine life and human health through investigating the heavy metal concentrations in the seawater. To determine the concentrations of As, Cr, Ni, Pb and Zn in seawater samples were collected in Kucuksu, Fenerbahce and Suadiye beaches in Istanbul near Asia at weekly intervals in the period between 19 October 2016 and 4 June 2017, laboratory analysis was conducted using ICP-MS was conducted. In addition to measuring pH and temperature onsite at the same time interval, pH and temperature were measured with dissolved oxygen from 18 November 2018 to 31 January 2019. The results showed that heavy metal concentrations, pH, temperature and dissolved oxygen in the Sea of Marmara do not pose a serious threat to aquatic life or human health.
Keywords: Marmara Sea; seawater quality; beaches; pH; recreation; DISSOLVED-OXYGEN; SEDIMENTS; POLLUTION; BAY